2021
DOI: 10.1186/s13195-021-00776-w
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Alzheimer’s disease biomarkers with a brief tablet-based cognitive battery: sensitivity to Aβ and tau PET

Abstract: Background β-amyloid (Aβ) and tau positron emission tomography (PET) detect the pathological changes that define Alzheimer’s disease (AD) in living people. Cognitive measures sensitive to Aβ and tau burden may help streamline identification of cases for confirmatory AD biomarker testing. Methods We examined the association of Brain Health Assessment (BHA) tablet-based cognitive measures with dichotomized Aβ -PET status using logistic regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…To improve early diagnosis of patients with progressive neurodegenerative disorders, efficient and accurate cognitive screens are needed for PCP across the world (Borson et al, 2013). Two previous studies The tablet-based BHA/BHS was previously validated at the clinical, neuroanatomical, and neuropathological level (Possin et al, 2018;Tsoy et al, 2021). The face-to-face test includes automated scoring and is easily used even by individuals with cognitive impairment and limited computer experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve early diagnosis of patients with progressive neurodegenerative disorders, efficient and accurate cognitive screens are needed for PCP across the world (Borson et al, 2013). Two previous studies The tablet-based BHA/BHS was previously validated at the clinical, neuroanatomical, and neuropathological level (Possin et al, 2018;Tsoy et al, 2021). The face-to-face test includes automated scoring and is easily used even by individuals with cognitive impairment and limited computer experience.…”
Section: Discussionmentioning
confidence: 99%
“…This validation study conducted in a sample of highly educated, White, and English-speaking patients in the United States showed that the tablet-based cognitive assessment (BHA) alone, as well as in conjunction with the informant survey, shows excellent combined sensitivity and specificity to typical and atypical presentations of mild neurocognitive disorder and dementia, outperforming the widely used MoCA (Possin et al, 2018). In addition, a longitudinal follow-up study demonstrated that the instrument is also sensitive to changes over time, even to very subtle changes in healthy individuals with positive amyloid status (Tsoy et al, 2021).…”
mentioning
confidence: 99%
“…26 The BHA has also demonstrated sensitivity to predict cerebral beta-amyloid (Aβ) status in cognitively normal individuals and associations with regional levels of tau positron emission tomography (PET) signal in the medial temporal lobe. 27,28 Harvard Aging Brain Study (HABS) researchers have also developed and/or validated several digital assessments with cognitively healthy adults, including tablet and digital pen-based measures. The HABS demonstrated that performance on a digitized clock drawing measure, the DCTclock TM , is able to distinguish between normal cognition and MCI and is associated with cerebral amyloid and tau pathology, suggesting utility for early detection.…”
Section: Introductionmentioning
confidence: 99%
“…BHA subtests have shown moderate to high correlations with reference standard neuropsychological tests, as well as medial temporal, frontal, parietal, and basal ganglia volumes 26 . The BHA has also demonstrated sensitivity to predict cerebral beta‐amyloid (Aβ) status in cognitively normal individuals and associations with regional levels of tau positron emission tomography (PET) signal in the medial temporal lobe 27,28 . Harvard Aging Brain Study (HABS) researchers have also developed and/or validated several digital assessments with cognitively healthy adults, including tablet and digital pen‐based measures.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, the development of unique and innovative technological approaches to detecting and tracking cognitive changes occurring early in conditions like AD is necessary. One such approach is the development of remotely administered computerized cognitive assessments ( 2 ). There have been several computerized cognitive tests that have been created and validated over the last decade ( 3 9 ), though notably the study and validation of computerized cognitive tests in culturally diverse samples needs significant attention moving forward ( 10 ).…”
Section: Introductionmentioning
confidence: 99%